Pengembangan Bumdes di Desa Modelidu Kecamatan Telaga Biru Kabupaten Gorontalo - Rajak, Fadila Abdul; Aneta, Asna; Dance Tui, Fenti Prihatini (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine (1) Development of BUMDes in Modelidu Village, Telaga Biru District which is related to organizational behavior, organizational structure and organizational process systems. (2) Supporting and inhibiting factors for the development of Bumdes in Modelidu Village, Telaga Biru District. The research method used is qualitative with a descriptive approach and data collection through observation, interviews and documentation. The research results show (1) The development of BUMDes in Modelidu Village, Telaga Biru District is related to organizational behavior, in terms of ethics, responsibility and leader motivation needs to be improved and developed. Regarding the organizational structure, in terms of overlapping duties and responsibilities and lack of focus on tasks in accordance with TUPOKSI. Regarding the organizational process system in terms of decision making, communication through socialization is also still lacking. (2) Inhibiting factors from a budget perspective, such as increasing additional capital and increasing public awareness regarding loan repayment, are still lacking. In terms of human resources, such as understanding computerization and work procedures is still lacking, and the amount of private support is limited. Supporting factors are the government's commitment to developing BUMDes further in the future, as well as the potential for natural resources such as agricultural management because the population of Modelidu Village is mostly farmers.